Improved Exopolymer Production by Chromohalobacter canadensis Cultures for Its Potential Cosmeceutical Applications - TOKSOY ÖNER, EBRU (MDPI, 2020)
Several exopolymers with different chemical composition and correspondingly variety in their physico-chemical properties from halophilic microorganisms have still been described, however, with a low production yield. Chromohalobacter canadensis 28 isolated from Pomorie saltern synthesized an unusual exopolymer (EP) containing 72% gamma-polyglutamic acid (PGA), an essential cosmeceutical additive. Current work suggests a novel approach for effective EP synthesis by C. canadensis 28 using continuous cultures. Highest production was observed at low dilution rates reaching a level of 2.1 mg/mL at D = 0.035, similar to those in batch cultures (2.34 mg/mL), however avoiding all disadvantages of discontinuous fermentation processes. At steady state, the total quantities of the synthesized EP after 48 h cultivation for the given equipment volume in D = 0.035 h(-1) and D = 0.075 h(-1) were 8.67 and 12 g, correspondingly, while it was 2.9 g for batch culture. Process parameters did not change after a ten-day run at D = 0.35 h(-1). A degree of purity of EP fraction received from continuous cultures was significantly increased up to 93-96%. A lack of cytotoxicity and high cell viability were observed for human dermal fibroblast cells after 24 h incubation with crude EP from C. canadensis 28 and purified PGA fraction that could suggest its high potential for cosmetic applications.
Keywords: halophilic bacterium; exopolymer; continuous cultivation; dilution rate; biocompatibility; INDUSTRIAL; ACID